Correctional “Free Lunch”? Cost Neglect Increases Punishment in Prosecutors - Aharoni, Eyal; Kleider-Offutt, Heather M.; Brosnan, Sarah F. (Frontiers in Psychology, 2021)
Prosecutors can influence judges’ sentencing decisions by the sentencing recommendations they make—but prosecutors are insulated from the costs of those sentences, which critics have described as a correctional “free lunch”. In a nationally distributed survey experiment, we show that when a sample of (N = 178) professional prosecutors were insulated from sentencing cost information, their prison sentence recommendations were nearly one-third lengthier than sentences rendered following exposure to direct cost information. Exposure to a fiscally equivalent benefit of incarceration did not impact sentencing recommendations, as predicted. This pattern suggests that prosecutors implicitly value incorporating sentencing costs but selectively neglect them unless they are made explicit. These findings highlight a likely but previously unrecognized contributor to mass incarceration and identify a potential way to remediate it.